Pengendalian Faktor Risiko Berdasarkan Peraturan Presiden Nomor 67 Tahun 2021 Tentang Penanggulangan TB Paru Di Kabupaten Takalar - Nurbiyanti. AB, A. Sri; Asrina, Andi; Hamzah, Wardiah (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the implementation of Presidential Regulation Number 67 of 2021 on Tuberculosis Control, focusing on the aspect of risk factor control in Takalar Regency. A qualitative descriptive approach was employed, utilizing in-depth interviews, observations, and documentation involving key informants, regular informants, and supporting informants engaged in the TB control program within the working areas of community health centers (Puskesmas) and the Takalar District Health Office. The findings reveal that risk factor control has been carried out through Health Promotion and Clean and Healthy Living Behavior (PHBS) education, active contact investigation, household condition assessment, the use of personal protective equipment, and cross-program collaboration. However, implementation remains constrained by low public awareness, fear of stigma, limited coordination with relevant local government agencies, and a shortage of health promotion personnel. Based on George C. Edwards III’s policy implementation theory, communication, resources, and organizational structure are identified as key challenges influencing the effectiveness of TB risk factor control in Takalar Regency.